Understanding health education needs of pregnant women in China during public health emergencies: a qualitative study amidst the COVID-19 pandemic - Su, Xiaojuan; Zhang, Yuezhen; Chen, Meide; Xu, Xiangyang; Liu, Guihua (Frontiers in Public Health, 2024)
Background: Public health emergencies impose unique challenges on pregnant women, affecting their physiological, psychological, and social well-being. This study, focusing on the context of COVID-19 pandemic in China, aims to comprehensively explore the experiences of pregnant women amidst diverse public health crises.Herein, we investigate the health education needs of pregnant Chinese women in regard to public health emergencies to provide a scientific foundation for the development of targeted health education strategies. Methods: Thirteen pregnant women were purposively selected, and the rationale for this sample size lies in the qualitative nature of the study, seeking in-depth insights rather than generalizability. Data collection involved semi-structured interviews, and the Colaizzi, which is a structured qualitative technique used to extract, interpret, and organize significant statements from participant descriptions into themes, providing a comprehensive understanding of their lived experiences. Results: The analysis yielded six prominent themes encompassing following six areas. Theme I:Personal protection and vaccine safety was analysed with 2 sub-themes( needs for personal protection knowledge, vaccine safety knowledge needs); Theme II:Knowledge of maternal health was analysed with 3 sub-themes( nutrition and diet, exercise and rest, sexual life)); Theme III:Knowledge of fetal health was analysed with 3 sub-themes( medications and hazardous substances, pregnancy check-ups, fetal movement monitoring); Theme IV:Knowledge of childbirth was analysed with 3 sub-themes( family accompaniment, analgesia in childbirth, choice of mode of delivery) ;Theme V:Knowledge of postpartum recovery was analysed with 1 sub-theme (knowledge of postnatal recovery); Theme VI:Knowledge sources of health education for pregnant women and their expectations of healthcare providers was analysed with 1 sub-theme( expectations of Healthcare providers). Sub-themes within each main theme were identified, offering a nuanced understanding of the multifaceted challenges faced by pregnant women during public health emergencies. The interrelation between sub-themes and main themes contributes to a holistic portrayal of their experiences. Conclusion: The study emphasizes the need for healthcare professionals to tailor health education for pregnant women during emergencies, highlighting the role of the Internet in improving information dissemination. It recommends actionable strategies for effective health communication, ensuring these women receive comprehensive support through digital platforms for better health outcomes during public health crises.